Beisbol en abril y otras historias - Soto, Gary.; Gomez Morin, Mauricio (Mexico : Fondo de Cultura Economica, 1995)
A collection of eleven short stories focusing on the everyday adventures of Hispanic young people growing up in Fresno, California.
Translation of: Baseball in April and other stories.
Keywords: Mexican Americans -- California -- Fiction